2022
DOI: 10.3389/fimmu.2022.835005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fibrosis in Inflammatory Bowel Disease and the Prospects of Mesenchymal Stem Cell Therapy

Abstract: Intestinal fibrosis is an important complication of inflammatory bowel disease (IBD). In the course of the development of fibrosis, certain parts of the intestine become narrowed, significantly destroying the structure and function of the intestine and affecting the quality of life of patients. Chronic inflammation is an important initiating factor of fibrosis. Unfortunately, the existing anti-inflammatory drugs cannot effectively prevent and alleviate fibrosis, and there is no effective anti-fibrotic drug, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 200 publications
0
31
0
Order By: Relevance
“…Leading edge genes that contributed most to the enrichment score were presented in heatmaps ( Figure 6 B,D). It is known that patients with inflammatory bowel disease usually develop intestinal fibrosis, which is marked by the activated epithelial-to-mesenchymal transition process [ 44 ]. Reactome GSEA showed the activation of pathways in the extracellular matrix organization, hemostasis and complement cascade ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leading edge genes that contributed most to the enrichment score were presented in heatmaps ( Figure 6 B,D). It is known that patients with inflammatory bowel disease usually develop intestinal fibrosis, which is marked by the activated epithelial-to-mesenchymal transition process [ 44 ]. Reactome GSEA showed the activation of pathways in the extracellular matrix organization, hemostasis and complement cascade ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal function was apparently disrupted in the xmrk fish, based on the deregulation of genes involved in digestion and absorption of nutrients from food, downregulation of genes maintaining epithelial cell barrier integrity, as well as downregulation of genes involved in general intestinal homeostasis. The activation of pathways in inflammation, ECM organization, EMT and hemostasis, which were found in the intestine of the xmrk fish, have also been reported in the inflammatory bowel disease in human patients [ 44 , 46 , 79 ]. Our GSEA analysis suggested common gene signatures between the xmrk intestine and human inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, TGF-β isoforms are abundant in the mammalian intestine, among which TGF-β1 is the most abundant isoform [ 31 , 32 ]. It plays a well-known role in intestinal immunity, and TGF-β activity is involved in the development of strictures during the pathogenesis of intestinal fibrosis, leading to complications in patients with IBD, especially CD [ 33 , 34 ]. Intestinal stricture in patients with CD is associated with elevated TGF transcript levels and excess accumulation of ECM proteins such as collagen and FN [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most evidence indicates that gastrointestinal tract fibrosis occurs only in previously or actively inflamed regions, implying that persisting inflammation is a necessary condition for developing fibrosis. In physiological conditions, acute inflammation is normally followed by healing with tissue restoration and functional recovery; in pathological conditions, the fibrotic process is established by the persistence of the inflammatory stimulus [ 4 , 5 , 6 , 7 , 8 , 9 ]. Many studies have demonstrated that TGF-β stimulates the activation and proliferation of fibroblasts, resulting in extracellular matrix deposition and fibrosis in several organs, including lungs, kidneys, liver, skin, and gut [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In physiological conditions, acute inflammation is normally followed by healing with tissue restoration and functional recovery; in pathological conditions, the fibrotic process is established by the persistence of the inflammatory stimulus [ 4 , 5 , 6 , 7 , 8 , 9 ]. Many studies have demonstrated that TGF-β stimulates the activation and proliferation of fibroblasts, resulting in extracellular matrix deposition and fibrosis in several organs, including lungs, kidneys, liver, skin, and gut [ 9 , 10 , 11 , 12 , 13 , 14 ]. Actually, inflammation causes the release of TGFβ, with the consequent activation of fibroblasts that differentiate into myofibroblasts, a cell type that has an intermediate phenotype between smooth muscle cells and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%